(3ZGjI GdShd aj TQM GdYTQg aUhds - (3jhfS Hf jhfS Hf YHO GdbGOQ Hf CMeO GdCKQi GdQTjOi GdTGaYjs; (3GHf GdeLOj , TgGH GdOjf CHh GdYHGS Hf GdeLOj,J (B850 (3g` s ((3eMeO GddjKi Hf jhSa Hf MSf s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CYWi ef TGA eG TGA CeG HYO gPG TQM dWja Ydi GdQSGdI GdYTQI aUhd GdehVhYI ai GdYed HGdQHY GdehShe HGdebfWQGJ s
(3BNQgG (B:s
(3agh GQJaGY GdchcH ai LgI GdZQH Ef cGf GdaVd ddHGbi ai LgI GdTQb Ef cGf dfUa GdbhS hGdMeO ddg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B221s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs